1979
DOI: 10.1242/dev.50.1.175
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cell killing by X-irradiation on pattern formation in the chick limb

Abstract: It has been suggested that positional information along the proximo-distal axis of the limb-bud is specified by time spent in the progress zone. Mesenchyme cells have been killed by X-irradiation, reducing the rate cells leave the zone. The time spent there by some cells is thus increased. When limbs, stage 18/19, stage 21, or tips of stage 24, are treated with increasing doses of X-irradiation, from 1000 rads to 2500 rads proximal structures are progressively lost, whereas distal ones— the digits—are relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…An analysis of defects in the formation of limbs after the X-irradiation of their buds in hen embryos showed that, 3.5 and 5.5 days after the start of incubation of eggs, predominantly the proximal and distal wing buds, respectively, are damaged [28]. The authors associate this with the death of chondrocyte precursors, a definite amount of which is necessary for the condensation of skeletal elements [29]. At earlier stages, the condensation of more proximal limb parts occurs, and at later stages the condensation of more distal limb parts takes place, which just explains different sensitivity to irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of defects in the formation of limbs after the X-irradiation of their buds in hen embryos showed that, 3.5 and 5.5 days after the start of incubation of eggs, predominantly the proximal and distal wing buds, respectively, are damaged [28]. The authors associate this with the death of chondrocyte precursors, a definite amount of which is necessary for the condensation of skeletal elements [29]. At earlier stages, the condensation of more proximal limb parts occurs, and at later stages the condensation of more distal limb parts takes place, which just explains different sensitivity to irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…This process is called primary neurulation, and it begins with an open neural plate, which creases inward until the edges fuse. In secondary neurulation, the tube forms by hollowing out of the solid precursor, then ends with the neural plate bending in distinct steps [36]. The embryonic disc begins flat and round, then elongates to form a wider cephalic part and narrow-shaped caudal end [37].…”
Section: Discussionmentioning
confidence: 99%
“…In Wolpert's group, Cheryll Tickle (FRS 1998) and Muriel Sampford X-irradiated chick embryos to kill large numbers of cells in the developing limb and deplete cells in the progress zone. Grafting these irradiated limbs to host embryos led to outgrowths that lacked proximal limb elements (humerus, radius and ulna) while developing fairly normal size distal elements (digits) (Wolpert et al 1979). Julian devised an astute mathematical model that appeared as the appendix to this paper, and supported the concept that time spent within the progress zone progressively specified increasingly distal positional values.…”
Section: The Wolpert Laboratorymentioning
confidence: 99%